Nurses’ Perspectives on Avoidable Readmissions of Geriatric Patients from Municipal Short-Term Care Units to Hospitals: - a qualitative study - Naguleswaran, Denusha; Sandsdalen, Tuva (Nordisk Tidsskrift for Helseforskning, 2025)
There is an increasing number of geriatric patients being readmitted from municipal services to the hospital. Readmissions that could have been avoided can be a burden for this patient group and the importance of preventing this is highlighted in key documents and previous research. This makes it necessary to identify experiences that can help reduce unnecessary readmissions. This study explores the experiences of nurses in municipal short-term wards with unnecessary readmissions of geriatric patients and supports previous research on this. Data was collected by individual semi-structured interviews with six nurses at two different municipal short-term wards. Findings that emerged were; «The hospital discharges patients too without plan for follow-up», «Patients with complex needs require advanced follow-up» and «Good interdisciplinary cooperation is important». The findings revealed that there are several factors that can contribute to increased unnecessary readmissions. Improvement measures should be aimed at these in both hospitals and municipal short-term wards.
Keywords: Nurse; experiences; unnecessary readmissions; municipal short-term departements; geriatric patients